Microbial life in the nascent Chicxulub crater - Schaefer, B.; Grice, Kliti; Coolen, Marco; Summons, R.E.; Cui, X.; Bauersachs, T.; Schwark, Lorenz; Böttcher, M.E.; Bralower, T.J.; Lyons, S.L.; Freeman, K.H.; Cockell, C.S.; et al. (GEOLOGICAL SOC AMER, INC, 2020)
The Chicxulub crater was formed by an asteroid impact at ca. 66 Ma. The impact is considered to have contributed to the end-Cretaceous mass extinction and reduced productivity in the world's oceans due to a transient cessation of photosynthesis. Here, biomarker profiles extracted from crater core material reveal exceptional insights into the post-impact upheaval and rapid recovery of microbial life. In the immediate hours to days after the impact, ocean resurge flooded the crater and a subsequent tsunami delivered debris from the surrounding carbonate ramp.  Deposited material, including biomarkers diagnostic for land plants, cyanobacteria, and photosynthetic sulfur bacteria, appears to have been mobilized by wave energy from coastal microbial mats. As that energy subsided, days to months later, blooms of unicellular cyanobacteria were fueled by terrigenous nutrients. Approximately 200 k.y. later, the nutrient supply waned and the basin returned to oligotrophic conditions, as evident from N2-fixing cyanobacteria biomarkers. At 1 m.y. after impact, the abundance of photosynthetic sulfur bacteria supported the development of water-column photic zone euxinia within the crater.